Comparative Proteomics of Three Species of Ammonia-Oxidizing Bacteria - Zorz, Jackie K.; Kozlowski, Jessica A.; Stein, Lisa Y.; Strous, Marc; Kleiner, Manuel (Frontiers in Microbiology, 2018)
Ammonia-oxidizing bacteria (AOB) are important members of terrestrial, marine, and industrial microbial communities and play a fundamental role in the Nitrogen cycle within these systems. They are responsible for the first step of nitrification, ammonia oxidation to nitrite. Although ammonia-oxidizing bacteria are widespread and essential to environmental and industrial systems, where they regularly experience fluctuations in ammonia availability, no comparative studies of the physiological response of diverse AOB species at the protein level exist. In the present study, we used 1D-LC-MS/MS proteomics to compare the metabolism and physiology of three species of ammonia oxidizing bacteria, Nitrosomonas europaea, Nitrosospira multiformis, and Nitrosomonas ureae, under ammonia replete and ammonia starved conditions. Additionally, we compared the expression of orthologous genes to determine the major differences in the proteome composition of the three species. We found that approximately one third of the predicted proteome was expressed in each species and that proteins for the key metabolic processes, ammonia oxidation and carbon fixation, were among the most abundant. The red copper protein, nitrosocyanin (NcyA) was highly abundant in all three species hinting towards its possible role as a central metabolic enzyme in AOB. The proteomic data also allowed us to identify pyrophosphate-dependent 6-phosphofructokinase as the potential enzyme replacing the Calvin-Benson-Bassham cycle enzyme Fructose-1,6-bisphosphatase missing in N. multiformis and N. ureae. Additionally, between species, there were statistically significant differences in the expression of many abundant proteins, including those related to nitrogen metabolism (nitrite reductase), motility (flagellin), cell growth and division (FtsH), and stress response (Rubrerythrin). The three species did not exhibit a starvation response at the proteome level after 24 hours of ammonia starvation, however the levels of the RuBisCO enzyme were consistently reduced after the starvation period, suggesting a decrease in capacity for biomass accumulation. This study presents the first published proteomes of N. ureae and N. multiformis, and the first comparative proteomics study of ammonia-oxidizing bacteria, which gives new insights into consistent metabolic features and differences between members of this environmentally and industrially important group.